Liver transplantation for primary biliary cholangitis (review) - I. M. Iljinsky; O. M. Tsirulnikova (Вестник трансплантологии и искусственных органов)
Primary biliary cholangitis (PBC) is an autoimmune liver disease resulting from the destruction and inflammation of intrahepatic bile ducts. This end-stage disease was once the most common cause of liver transplantation. The use of ursodeoxycholic and obeticholic acids as a first-line and second-line treatment, respectively, slows down the disease. However, treatment is not effective in about 40% of PBC patients, and the disease may progress to cirrhosis and end-stage liver disease. These patients undergo liver transplantation to save their lives. After surgery, recurrent PBC can develop in a milder form and rarely requires liver retransplantation.